Catalytically Active Iron(IV)oxo Species Based on a Bis(pyridinyl)phenanthrolinylmethane. Issue 10 (30th March 2020) - Hüppe, Henrika M.; Keisers, Kristina; Fink, Fabian; Mürtz, Sonja D.; Hoffmann, Alexander; Iffland, Linda; Apfel, Ulf‐Peter; Herres‐Pawlis, Sonja
Abstract: Starting from the mononuclear iron(II) complex [Fe(MeCPy2 Phen)(MeCN)2 ] 2+, a non‐heme Fe(IV)oxo complex [Fe IV (MeCPy2 Phen)O] 2+ was synthesized via oxidation with meta ‐chloroperoxybenzoic acid (mCPBA). The Fe(IV)oxo complex was characterized using UV/Vis spectroscopy, Mößbauer spectroscopy and CSI mass spectrometry. The ability of this species to oxidize C−H bonds was tested with cyclohexane and adamantane as model substrates. For cyclohexane, an alcohol‐to‐ketone ratio ( A / K ) of 6.1 and efficiencies up to 55 were obtained. In case of adamantane, the ratio of tertiary over secondary products (3°/2°) is 38. In combination, this indicates the iron(IV)oxo complex being the catalytically active species. Abstract :